2010
DOI: 10.1016/j.lindif.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

What to do when feeling bored?

Abstract: The goal of this study was to explore different strategies for coping with boredom. A questionnaire was developed targeting two dimensions of coping, namely approach versus avoidance oriented coping and cognitive versus behavioral oriented coping. First, based on the responses of 976 students (51% female) from grades 5 to 10, the structure of the coping with boredom scales was verified by confirmatory factor analysis. In a second step, 3 different boredom-coping groups were identified by latent profile analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
108
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 57 publications
(100 reference statements)
8
108
0
1
Order By: Relevance
“…Cognitive avoidance and behavioral avoidance strat egies involve cognitive and physical disengagement, respectively, from boring situations. Cognitive approach strategies were negatively relat ed to frequency of boredom and positively associated with value in learning (Nett et al, 2010(Nett et al, , 2011; whereas, both cognitive avoidance and behavioral avoidance coping were positively related to the occur rence of boredom and negatively related to effort in learning.…”
Section: Boredom Coping Strategiesmentioning
confidence: 92%
See 4 more Smart Citations
“…Cognitive avoidance and behavioral avoidance strat egies involve cognitive and physical disengagement, respectively, from boring situations. Cognitive approach strategies were negatively relat ed to frequency of boredom and positively associated with value in learning (Nett et al, 2010(Nett et al, , 2011; whereas, both cognitive avoidance and behavioral avoidance coping were positively related to the occur rence of boredom and negatively related to effort in learning.…”
Section: Boredom Coping Strategiesmentioning
confidence: 92%
“…The Evader profile was com mon for Chinese students along with two additional coping profiles: In frequent Copers who were low on all coping strategies and Reformers who were high on all strategies except behavioral avoidance. In Nett et al (2010Nett et al ( , 2011 the Reappraiser profile was consistently the most adaptive as evidenced by lower boredom, sustained interest and effort, and higher levels of agreeableness and conscientiousness. In contrast, Reappraisers and Criticizers did not differ in their perceptions of bore dom in Tze, Klassen, Daniels et al's (2013) research and Criticizers actu ally reported significantly more intrinsic motivation than Reappraisers.…”
Section: Boredom Coping Strategiesmentioning
confidence: 96%
See 3 more Smart Citations